Genetic characterisation of childhood B‐other‐acute lymphoblastic leukaemia in UK patients by fluorescence in situ hybridisation and Multiplex Ligation‐dependent Probe Amplification. (21st October 2021) - Schwab, Claire J.; Murdy, Daniel; Butler, Ellie; Enshaei, Amir; Winterman, Emily; Cranston, Ruth E.; Ryan, Sarra; Barretta, Emilio; Hawking, Zoe; Murray, James; Antony, Grace; Vora, Ajay; et al.
Summary: While next‐generation sequencing technologies provide excellent strategies to screen for newly defined genetic abnormalities of prognostic or therapeutic significance in patients with B‐other‐acute lymphoblastic leukaemia (ALL), they are not widely available. We used a dual screening approach, incorporating fluorescence in situ hybridisation (FISH) and Multiplex Ligation‐dependent Probe Amplification (MLPA), to establish the frequency and long‐term outcome of a representative cohort of specific subgroups of B‐other‐ALL recruited to the childhood ALL trial, UKALL2003. We focussed on abnormalities of known prognostic significance, including ABL‐class fusions and ERG deletions, as a surrogate marker for DUX4 ‐rearranged ALL. ABL‐class fusions accounted for 4% of B‐other‐ALL and were associated with high levels of minimal residual disease (MRD; 14/23 with MRD >5%) and a high relapse rate (55·7%) following treatment without tyrosine kinase inhibitor (TKI), confirming the importance of prospective screening with a view to incorporating TKI into therapy. Patients with deletions of ERG ( 10% of B‐other‐ALL) had a 10‐year event‐free‐survival of 97·2%, validating previous reports of their excellent outcome. Rearrangements of ZNF384, MEF2D and NUTM1 were observed at low frequencies. Here, we estimate that approximately one third of B‐other‐ALL patients can be reliably classified into one of the known genetic subgroups using our dual screening method. This approach is rapid, accurate and readily incorporated into routine testing.